Cryptobiota associated to dead Acropora palmata (Scleractinia: Acroporidae) coral, Isla Grande, colombian Caribbean - Moreno-Forero, Silvia K; Navas S., Gabriel R; Solano, O David (Revista de Biología Tropical, 1998)
Cryptobiota of dead fragments of five branehes in live position and five fallen pieces of the coral Acropora palmata each one of approximate Idm3, eovered by filamentous algae were extraeted from the north reef erest of Isla Grande (Colombian Caribbean), in April 1991. There were three groups of organisms according lo size and position (on and wi!hin the coral): 1) mobile epibenthos, mainly microcrustaceans ¡hat ¡ive among the fIlamentous algae 2) boring microcryptobiota, located in lhe layer between ¡he epilithic organisms and the coral skeJeton